Pengaruh Strategi Pembelajaran Crossword Puzzle Terhadap Hasil Belajar Siswa Kelas IV IPS SD Negeri Minasa Upa Makassar - Chaerunnisa. G; Suardi Suardi; Syarifah Aeni Rahman (Departement of Mathematics Education, 2024)
The main problem in this research is how the crossword puzzle learning strategy influences the learning outcomes of class IV students in social studies subjects at SD Negeri Minasa Upa Makassar. This research aims to determine the effect of the Crossword Puzzle learning strategy on the learning outcomes of class IV students in social studies subjects at SD Negeri Minasa Upa Makassar. This type of research is a pre-experimental design with a one group pretest-posttest design. The subjects in this research were 27 class IV students at Minasa Upa Public Elementary School, Makassar. Data collection techniques were carried out using learning outcomes tests and observation data. The collected data was analyzed quantitatively using descriptive statistics and inferential statistics. The results of inferential statistical research using the normality test of learning outcomes for students who taught by applying the crossword puzzle strategy, obtained a significant value in the pretest of 0.245 and a posttest of 0.398. The significant value obtained was >0.05 so that the data was normally distributed. Based on the results of this research, it can be concluded that there is an influence on the learning outcomes of class IV students in social studies subjects at SD Negeri Minasa Upa Makassar.